Analisis Profitabilitas Terhadap Kinerja Keuangan PT Adaro Energy.Tbk Sebelum dan Sesudah Pandemi - Nurul Hidayah; Muhammad Aqdam Baihaqi; Nofita Rahmawati; Adelina Citradewi (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2022)
The profitability ratio is used to measure the effectiveness of management of the output of returns obtained by sales and investment to know the company's ability to generate profits during a certain period and carry out the duties of its operations. This study aims to determine the value of Net Profit Margin (NPM), Gross Profit Margin (GPM), Return On Assets (ROA), and Return On Equity (ROE) during the pandemic and after the covid-19 pandemic. This study uses a descriptive method and the data collection technique in this research is a sampling technique. Net Profit Margin (NPM) tends to increase, this is because the components of net profit and income also increase. Gross Profit Margin (GPM) tends to increase. This is because the components of gross profit and income have also increased. Return on Assets (ROA) tends to increase, this is because the components of net income and total assets also increase. Return On Equity (ROE) in 2015 to 2016 has increased, this is because the components of net income and equity also increased